The consumer's experience («Erlebnis») in contemporary shopping malls: Ritual reproduction and consumer's identity - Λάλλας, Δημήτρης (The Greek Review of Social Research, 2012)
In this article, the relation of new form of experience, that is promoted and searched for in contemporary shopping malls, with these commercial environments is examined. The safe, predictable and rich in commercial and spectacular references and practices experience, at these shopping places, seems to be a «matter» of ritual procedure. Malls, as ritual places, as fields of roles' performance and as «symbolic mediators», accommodate, foster and provoke, in its interior, self-contained microcosm, rites which attribute to visitors-consumers-insiders the identity of «sufficient consumer».